The Dynamic Linkage between Technological Innovation and CO2 emissions in Malaysia: An ARDL Bound Approach - Ali, Wajahat; Abdullah, Azrai; Abdullah, Azrai; Azam, Muhammad; Azam, Muhammad (International Journal of Energy Economics and Policy, 2016)
Environmental degradation and climate change are the main challenges encountered to achieve the predominant objective of sustainable development. There has been voluminous work done in this area, but the policies adopted and the empirical relationship between the determinants of CO2 emissions are not clear to handle the problem. There exists a theoretical and empirical contradiction in the literature on the relationship between the variables under the study. Thus, the current study investigates the relationship between carbon dioxide (CO2) emissions and its determinants namely economic growth, energy consumption, financial development, and technological innovations for Malaysia between 1985 and 2012. To achieve the objective of long-run relationship the autoregressive distributed lagged (ARDL) model is used for parameter estimation. The empirical results reveal that technological innovation is having a negative but insignificant relationship with environmental pollution in Malaysia during the period under study. The study also indicates that higher economic growth improves the environmental quality in the long-run and is in line with the Environmental Kuznets Curve (EKC) hypothesis. In a similar vein, the results indicate that financial sector development will lessen the CO2 emissions, thus, improving the quality of the environment in Malaysia. The short-run results reveal no evidence of the validation EKC hypothesis. Furthermore, the study applied Granger causality approach for causal relationship and found bidirectional causality running between economic growth and CO2 emissions and between technological innovation and CO2 emissions in the long-run. The study also found that the impact of energy consumption in the short-run is environmentally friendly. Moreover, the results indicate a short-run bidirectional causality running between energy consumption and economic growth and also between economic growth and technological innovation. Keywords: CO2 emissions, EKC, technological innovation, ARDL, Malaysia JEL Classifications: C32, O52, Q43, Q50